2011
DOI: 10.1080/03088839.2011.588258
|View full text |Cite
|
Sign up to set email alerts
|

Pursuing maritime education: an empirical study of students’ profiles, motivations and expectations

Abstract: This study reveals the profiles, motivations, and expectations of students pursuing undergraduate maritime programmes. Although a number of tertiary institutions offer maritime programmes, the characteristics and structures of the demands for such programmes remain under-researched. This paper illustrates and discusses the results of a survey completed by students pursuing undergraduate programmes in maritime business and management at three universities in Asia and Europe, and compares them with the findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 20 publications
2
28
0
Order By: Relevance
“…√ √ √ Pallis and Adolf (2011) √ √ Amante (2003) √ √ √ √ √ Taylor (2012) √ √ Nas and Çelik (2012) √ √ Analyzing all of these studies in the literature in terms of data used in research, it is revealed that each of them operates on a different number of data sets. The study conducted by Ellis and Sampson (2008) who reviewed the profile of crewing of the world fleet outlining age, rank, nationality and also the types of vessel they are employed on comprise of 4240 vessels and 80863 seafarers.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…√ √ √ Pallis and Adolf (2011) √ √ Amante (2003) √ √ √ √ √ Taylor (2012) √ √ Nas and Çelik (2012) √ √ Analyzing all of these studies in the literature in terms of data used in research, it is revealed that each of them operates on a different number of data sets. The study conducted by Ellis and Sampson (2008) who reviewed the profile of crewing of the world fleet outlining age, rank, nationality and also the types of vessel they are employed on comprise of 4240 vessels and 80863 seafarers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Data collection in this study made via interviews and questionnaires. Pallis and Adolf (2011) conducted a study to reveal the profiles, motivations and expectations of students pursuing undergraduate maritime programs. The study discussed the results of a survey fulfilled by students pursuing undergraduate programs in maritime business and management at three universities in Asia and Europe and the findings also compared with database examining of postgraduate students within the same institutions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies (Ng et al 2009;Pallis and Ng 2011) explore motivations and expectations among seafarers enrolled in formal MET programs. These studies were conducted in an international context and do not directly discuss the role of sail training techniques in an MET program or curriculum.…”
Section: 2mentioning
confidence: 99%
“…seafarers, staff in shipping companies, shipping forwarders, shipping agents, ship-broker, port authorities, etc.) must have "good" English abilities (including listening, speaking, reading, writing) (Pallis and Ng, 2011). Therefore, proficiency in English is a prerequisite for employment in the shipping industry.…”
Section: Introductionmentioning
confidence: 99%
“…Understandably therefore, shipping development and education have historically occupied a central and key position in university education in Taiwan. For those students who go on to work in the shipping industry, it is essential they have a strong command of the English language (Pallis and Ng, 2011), as this is the medium in which communication is most commonly undertaken in the shipping industry. However, in Taiwan, Chinese is the first language and English is a second or other language, and there is, thus, a perennial challenge faced by students and lecturers in developing students' English for the shipping industry.…”
Section: Introductionmentioning
confidence: 99%